Yield and Nutritional Quality of Green Leafy Lettuce (Lactuca sativa L.) under Soilless Culture System Using Various Composition of Growing Media and Vermicompost Rates - Nurhidayati Nurhidayati; Masyhuri Machfudz; Abdul Basit (Universitas Sebelas Maret, 2021)
Soilless culture system (SCS) production is preferred because it is more hygienic and highly nutritious and free of chemical pesticides. However, the application of organic fertilizers in SCS for green vegetable cultivation is still rarely used. This study was to test various growing media compositions and vermicompost rates on green lettuce's nutritional quality. Four types of growing media (using the mixture of cocopeat, zeolite, rice husk biochar and sand) and five levels of vermicompost rates (50-250 g pot-1) were tested. The greatest total fresh weight and marketable yield were found using 55% cocopeat, 30% rice husk biochar and 15% sand with a vermicompost rate of 250 g pot-1. The highest nutritional quality of green lettuce as measured by the highest content of chlorophyll A, B, the total chlorophyll and calcium (Ca) was found in the composition of cocopeat 55%, zeolite 30% and sand 15%. As was, the highest mineral content of of potassium (K) and phosphorus (P). Good quality lettuce was found in growing media using 30% biochar with a vermicompost rates of 200-250 g pot-1 and growing media using 30% zeolite with a vermicompost rates of 150-200 g pot-1. Thus, the admixtures of biochar and zeolite into the cocopeat substrate for the soilless culture system of green leafy lettuce significantly affected yield and nutritional quality.